Analysis of lactation specific demographic parameters of Tharparkar cattle - MAHER, DINESH; GUPTA, A K; BHAKAT, MUKESH; UPADHYAY, ARPAN; MIR, MOHSIN AYOUB (The Indian Journal of Animal Sciences, 2015)
The most important factor in milking herd is to maintain lactating cows in subsequent lactations, which depends upon stayability of lactating animals. Therefore a study on records of 168 Tharparkar females maintained during 1980-2010 at Livestock Research Centre, National Dairy Research Institute, Karnal (Haryana) were conducted to estimate the lactation specific demographic parameters.The results depicted that the survival and loss rates in first lactation were 70% and 30%, respectively. In fifth lactation survival rate was highest (76%) and disposal rates were the lowest (24%). There was no definite trend of survival and disposal rate across different lactations. Stayability results showed that the probability of an animal to survive in the herd decreased with the increasing number of lactations. The stayability for the first lactation was one whereas, the values revealed a consistent decline in subsequent lactations. Age distribution of cows present in the herd (px) for first lactation was 0.314 and 0.217, 0.154, 0.107, 0.069, 0.053, 0.034, 0.025, 0.015, 0.009, 0.003, 0.001 in subsequent lactations. Around one third of the total herd comprised of the first calvers (31%) and one fifth belongs to the females of second lactations (21.7%). Overall the herd of lactating cows comprised of 79.2% of animals in lactations up to fourth parity. Age distribution of cows left the herd (qx) in first and subsequent lactations was 0.300 and 0.201, 0.167, 0.099, 0.053, 0.054, 0.029, 0.029, 0.016, 0.019, 0.005 and 0.005, respectively. From the results it could be concluded that the cows in first lactation was expected to remain in the herd for 2.24 lactations more. Expected herd life decreased with the increase in lactation order.